Cavernous hemangioma of the parotid gland - Ravi Hari Phulware; Amrita Talwar; Arvind Ahuja (Autopsy and Case Reports, 2023)
Cavernous hemangioma (CH), or cavernoma, is a type of benign tumor occurring mostly in the brain, liver, skin, and retina.1,2 Although less commonly, CH can also occur in the spine, orbit, gastrointestinal tract, skeletal muscle, and long bones.1 CH comprises a cluster of abnormally dilated blood vessels that form a mass or lesion.2,3